A Case of Cosecretion of Parathyroid Hormone-Related Protein and 1,25-Dihydroxyvitamin D in Small Cell Lung Carcinoma Presenting as Symptomatic Hypercalcemia - John Pueringer; Danich Qadir; James Love; Ryan Knodle; Michael Gianarakis; Gabriela Mendez; Frank Weinberg (Annals of Internal Medicine: Clinical Cases)
A 75-year-old man presented with altered mental status in the setting of hypercalcemia. Computed tomography imaging showed a new right upper lobe lung lesion and extensive metastatic disease of the spine. Biopsy specimens of the lung revealed small cell carcinoma. Laboratory tests revealed hypercalcemia, low parathyroid hormone levels, and elevated parathyroid hormone-related protein, 1,25-dihydroxyvitamin D, and chromogranin A levels. We review a case of cosecretion of parathyroid hormone-related protein and 1,25-dihydroxyvitamin D by small cell carcinoma of the lung presenting as symptomatic hypercalcemia of malignancy, for which diagnosis can be challenging. To our knowledge, this would be the first case reported in the medical literature.